Sociology, culture and family planning : a conceptual, experiential and interactive approach - San Juan, Wilfredo R.; Centeno, Ma. Luz J. (Pasig City, Philippines : UNLAD Publishing House, 2011)
This book is the authors' contribution to the learners of Sociology- our way of sharing our classroom experiences, research, and our person. It is every educator's wish to influence his or her students to be active participants in the transformation of society into a better place for generations to come. We believe that the classroom is a potent venue for both teachers and students to learn about the basics of social life, social interactions, social issues and society in general. The book also hopes to influence the learners who would be future professionals, lawmakers, government officials and social development planners to be more responsive to the plight of the oppressed and culturally deprive sectors of the society.
Part 1 - Introduction to sociology -- Chapter 1 - Sociology as a humanistic and scientific discipline -- Chapter 2 - Theoretical paradigms on society and social behavior -- Chapter 3 - Sociological perspectives and sociological inquiry -- Part 2 - Culture and other basic concepts -- Chapter 4 - Culture -- Chapter 5 - Similarity and diversity in culture -- Chapter 6 - Philippine values -- Chapter 7 - Socialization and personality -- Chapter 8 - Deviant behavior -- Chapter 9 - Social groups and social organizations -- Chapter 10 - Social interaction and social processes -- Chapter 11 - Collective behavior and social movements -- Chapter 12 - Social stratification and social mobility -- Chapter 13 - Ethnic groups and racism -- Chapter 14 - Social change and globalization -- Part 3 - Communities and population -- Chapter 15 - Rural and urban communities -- Chapter 16 - Population and demography -- Part IV - Basic social institutions -- Chapter 17 - Religion and society -- Chapter 18 - Government and law -- Chapter 19 - Economy -- Chapter 20 - Education -- Chapter 21 - Marriage and the family -- Part V - Family planning and responsible parenting -- Chapter 22 - Family planning -- Chapter 23 - Responsible parenting.
Includes bibliographical references.
Keywords: SOCIOLOGY -- FAMILY PLANNING